2020
DOI: 10.1038/s41598-020-58682-4
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of facial contour asymmetry after conventional two-dimensional versus computer-assisted three-dimensional planning in cleft orthognathic surgery

Abstract: Computer-assisted 3D planning has overcome the limitations of conventional 2D planning-guided orthognathic surgery (OGS), but difference for facial contour asymmetry outcome has not been verified to date. This comparative study assessed the facial contour asymmetry outcome of consecutive patients with unilateral cleft lip and palate who underwent 2D planning (n = 37)-or 3D simulation (n = 38)-guided OGS treatment for correction of maxillary hypoplasia and skeletal Class III malocclusion between 2010 and 2018. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 66 publications
(121 reference statements)
0
29
0
1
Order By: Relevance
“…Over the past 4 decades, all technical details that could attenuate the surgical burden of care (ie, reduction in the number of revision surgeries, clinical appointments, and overall treatment time) during the development and maturity phases have been combined to compose our current cleft surgical protocol (Denadai and Lo, 2019; Pai et al, 2019; Denadai et al, 2020). The single-splint concept based on patient-centered planning and execution has been consistently reproduced by treating surgeons in our center, resulting in the minimization of cleft stigma (Supplementary Material 7), achieving a maximum benefit–risk equilibrium as required for elective surgery, improved symmetry (overall facial symmetry, midline, and contour), clinically stable results (relapse within the clinically acceptable range), and minimal requirement of revision surgery (Lonic et al, 2016; Chou et al, 2019; Liao et al, 2019; Seo et al, 2019; Hsu et al, 2020). The 3D digital environment of OGS treatment supports the complete integration of functionally and aesthetically rehabilitated patients into society (Supplementary Material 8), which is the goal of long-term cleft care (Denadai and Lo, 2019; Pai et al, 2019; Denadai and Lo, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the past 4 decades, all technical details that could attenuate the surgical burden of care (ie, reduction in the number of revision surgeries, clinical appointments, and overall treatment time) during the development and maturity phases have been combined to compose our current cleft surgical protocol (Denadai and Lo, 2019; Pai et al, 2019; Denadai et al, 2020). The single-splint concept based on patient-centered planning and execution has been consistently reproduced by treating surgeons in our center, resulting in the minimization of cleft stigma (Supplementary Material 7), achieving a maximum benefit–risk equilibrium as required for elective surgery, improved symmetry (overall facial symmetry, midline, and contour), clinically stable results (relapse within the clinically acceptable range), and minimal requirement of revision surgery (Lonic et al, 2016; Chou et al, 2019; Liao et al, 2019; Seo et al, 2019; Hsu et al, 2020). The 3D digital environment of OGS treatment supports the complete integration of functionally and aesthetically rehabilitated patients into society (Supplementary Material 8), which is the goal of long-term cleft care (Denadai and Lo, 2019; Pai et al, 2019; Denadai and Lo, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Compared with conventional 2-dimensional imaging-aided stone model surgery, 3D virtual surgery has revolutionized the perioperative workup (ie, laser scanned dentition, 3D cephalometric tracings, digital occlusion set-up, and computer-generated surgical splint) and outcomes (ie, time efficiency, accuracy, facial contour symmetry, and cost-effectiveness) of OGS care (Lonic et al, 2016; Ho et al, 2017; Wu et al, 2017; Hsu et al, 2020). The cone-beam computed tomography-based 3D diagnostic pathway (Supplementary Material 1) provides the opportunity for an orthodontic-surgical collaborative approach (Wu et al, 2017).…”
Section: From 2-dimensional To 3d Settingmentioning
confidence: 99%
“…Wilson et al [28] reported that there was a high degree of conformity when comparing the virtual surgical planning to the actual postoperative outcomes, except for some incongruent results of maxillary vertical and mandibular sagittal movement. Furthermore, 3D virtual planning also has advantages for soft tissue simulation with facial contouring, and Hsu et al [33] reported that 3D planning presents superior facial contour symmetry outcomes than two-dimensional (2D) planning in unilateral cleft patients. The use of a fabricated osteotomy cutting guide and prebended fixation plates based on virtual surgical planning increases the feasibility of planned osteotomies and repositioning of the maxillomandibular segment, thereby saving time [34].…”
Section: Virtual Surgical Planningmentioning
confidence: 99%
“…Computerized planning in orthognathic surgery allows surgeons to carry out comprehensive evaluation of anatomical structures of the surgical field. In asymmetric patients, VSP can be used to diagnose presurgical problems and can predict the postoperative 3D position of osteotomized segments, thereby predicting redundant asymmetry after surgery (26). At the same time, the need for dental decompensation after surgery can also be visualized and it is possible to reflect the magnitude of overcorrection to VSP in advance (1).…”
Section: Practical Advantage Of Computerized Surgical Planning In Orthognathic Surgerymentioning
confidence: 99%